ANALISIS PERBEDAAN JUMLAH NEUTROFIL ANTARA ANAK DOWN SYNDROME DAN ANAK SEHAT - Studi Pada SLB-C Widya Bhakti Semarang dan Mi Mirfa’ul Ulum - Riezqia Ayu Wulandari; Sandy Christiono; Niluh Ringga (Odonto : Dental Journal, 2017)
Background: Down syndrome (DS) is a congenital disorder caused by abnormalities of chromosome 21, resulting in migration defect of neutrophils, specifically in GCF as a marker of increasing periodontal infection. This study aimed to analyze the difference in neutrophil numbers between down syndrome and healthy children.Method: This research was an analytic observational with cross sectional design, and divided into two groups. The control group is consisted of healthy children and the other is consisted of down syndrome children. GCF was taken using paper point number 45-50 for 30 seconds, then it smeared into object glass and painted with giemsa staining. Observations was done by light microscopy with 1000 times magnification.Result: The result of studies with p<0.05 was indicating a significant difference of neutrophil numbers between children with down syndrome and the healthy group.Conclusion: This study concluded that there was a difference in neutrophil numbers due to the migration defect of neutrophils in children with down syndrome, that can cause proneness to periodontal infections.